2019
DOI: 10.1021/acs.jpca.9b02105
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Free Energy Profiles of Uracil and Cytosine Reactions with Formaldehyde

Abstract: Simple polymers can be potentially formed by the cooligomerization of pyrimidine nucleobases, uracil and cytosine, with the small molecule formaldehyde. Using density functional calculations, we have constructed a free energy map outlining the thermodynamics and kinetics for (1) the addition of formaldehyde to uracil and cytosine to form hydroxymethylated uracil (HMU) and hydroxymethylated cytosine (HMC), (2) the deamination of cytosine and HMC to uracil and HMU, respectively, and (3) the initial oligomerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…36 In our previous work requiring such daisy-chain S N 2 transition states, our calculated barriers were in the ∼35 kcal/mol range, likely overestimated by 10 or more kcal/mol given that the reactions studied were somewhat facile at room temperature experimentally. 11,12,32 Thus, in the present work, although our calculated barrier for 39 → 46 is ∼40 kcal/mol, the experimental barrier for this S N 2 reaction is likely 30 kcal/ mol (or possibly lower). There is a route to glycine, but it would require higher temperatures to be kinetically accessible.…”
Section: ■ Computational Methodscontrasting
confidence: 51%
See 2 more Smart Citations
“…36 In our previous work requiring such daisy-chain S N 2 transition states, our calculated barriers were in the ∼35 kcal/mol range, likely overestimated by 10 or more kcal/mol given that the reactions studied were somewhat facile at room temperature experimentally. 11,12,32 Thus, in the present work, although our calculated barrier for 39 → 46 is ∼40 kcal/mol, the experimental barrier for this S N 2 reaction is likely 30 kcal/ mol (or possibly lower). There is a route to glycine, but it would require higher temperatures to be kinetically accessible.…”
Section: ■ Computational Methodscontrasting
confidence: 51%
“…Although water may be reactant or product in hydration/dehydration reactions, concentration corrections are not included in this map, the advantages and disadvantages of which are discussed in detail in previous work. 9,12,22 Our protocol was previously put to the test with a detailed comparison of our computational results with NMR measurements for the self-oligomerization of a 1 M solution of glycolaldehyde; 9 our calculated equilibrium concentrations of the dominant species in solution (monomers and dimers) agreed very well with experiment. In addition, our calculations allowed us to successfully predict the concentrations of trimers in solution, 2 orders of magnitude lower than the monomers.…”
Section: ■ Computational Methodsmentioning
confidence: 55%
See 1 more Smart Citation
“…The six-membered heteroatom ring of uracil is planar, resembling aromatic molecules of benzene or pyridine. Due to its importance in nature and interesting biological activities, there have been many theoretical and experimental studies on uracil and its derivatives, for example, as reported in references [18,[22][23][24][25][27][28][29][30][31][32][33]. The main scientific problems analyzed were structure [26,34,35], energetics [34,36,37], vibrational [27][28][29][30][31]38] and NMR spectra [33,[39][40][41].…”
Section: Figurementioning
confidence: 99%
“…Pyrimidine nitrogen bases, including uracil and its 5-halogeno derivatives, can potentially exist in several tautomeric forms ( Figure 2 ) as free molecules [ 22 , 23 , 24 , 25 ] and in solution [ 26 ]. The six-membered heteroatom ring of uracil is planar, resembling aromatic molecules of benzene or pyridine.…”
Section: Introductionmentioning
confidence: 99%